IDENTIFIKASI BAWAH PERMUKAAN LAPANGAN MINYAK“HUF” SUMATERA SELATAN UNTUK MENDELINIASI STRUKTUR CEKUNGAN HIDROKARBON BERDASARKAN DATA GAYABERAT - Ade Setiawan; Bagus Sapto Mulyatno (Engineering Faculty Universitas Lampung, 2018)
Oil field research in regional Banyuasin “HUF” , South Sumatra have been done by the gravity data with objective of knowing fault structure based on analysis of hydrocarbon SVD and knows hollow structure based on the 3D model of the Bouguer Anomaly and Residual Anomaly. Study areas had Bouguer Anomaly between 13 mgal up to 33 mgal to the interval 1 mgal, where the value of Bouguer Anomaly high have a range value 26 mgal up to 33 mgal which is in the direction of west. While the low value of Bouguer Anomaly have a range value 13 mgal to 20 mgal that is in the east. To knew the existence of structure fault, filtering Second Vertical Derivative (SVD) on a Bouguer Anomaly, Regional and Residua mapl.Pattern of structure fault indicated the contours of a zero value and between the high and low contours. From the results of the analysis SVD Complete Bouguer Anomaly and SVD Residual Anomaly there were 4 (four) fault, while from SVD Regional Anomaly there are 3 (three) fault. 3D modeling the Residual Anomaly were conducted to prove the existence of the fault SVD analyzed based on the results of the analysis and to know the hydrocarbon basin. Based on the results of the inversion of 3D the Residual Anomaly, basin was found in the depth of 1500 m – 3000 m with a value of the density ranges from 2.24 gram/cc until 2.32 gram/cc which identified as sandstone basin.